Nordic Design Cultures in Transformation, 1960-1980 Revolt and Resilience - Fallan, Kjetil; Zetterlund, Christina; Munch, Anders V. (Routledge Research in Design History, 2023)
Covering the 1960s and 1970s, this volume explores new ways of investigating, comparing and interpreting the different domains of design culture across the Nordic countries. Challenging the traditional narrative, this volume argues that the roots of the most prominent features of Nordic design's contemporary significance are not to be found amongst the objects for the home collectively branded as 'Scandinavian Design' to great acclaim in the 1950s, but in the discourses, institutions and practices formed in the aftermath of that oft-told success story, during the turbulent period between 1960 and 1980. This is achieved by employing multidisciplinary approaches to connect the domains of industrial production, marketing, consumption, public institutions, design educations, trade journals as well as public debates and civic initiatives forming a design culture. This book makes a significant contribution to current, international agendas of historiographical critique focusing on transnational relations and the deconstruction of national design histories. This book will be of interest to scholars in design, design history and Scandinavian studies.